Dieta alimentar da onça-parda, Puma concolor (Linnaeus, 1771), em uma unidade de manejo florestal em Borebi-SP - Rongetta, Amanda Moretti [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In Brazil, the puma, Puma concolor (Linnaeus, 1771) is present in all biomes. The ability of pumas in suit different types of habitats the species has led increasingly to use disturbed areas in search of food and shelter, especially areas of reforestation with exotic species such as pine and eucalyptus. The main threats encountered by cats are the fragmentation and modification of habitat, mainly in the Atlantic Forest and Cerrado biomes, and indiscriminate hunting. The diet of a species is one of the most basic aspects of their ecology, but permeates almost all ecological parameters, such as the social system, and spatial patterns of activity, so it can be considered essential for understanding their ecology and can assist in management plans and conservation areas and species. The objective of this study is to characterize the diet of pumas in a forest management unit that is situated in an area of contact between Cerrado and Atlantic Forest through eschatological material. Samples were collected from April to September in 2007 and 2008, in a forest management unit in the municipality of Borebi-SP, totaling 10 amostas. After the analysis of the material obtained 16 occurrences of 8 food items with the largest percentage of occurrence was mammals (62.5%), mainly Dasypus novemcinctus (Linnaeus, 1758), considered as the main food item according to frequency of occurrence of and percentage of prey biomass consumed, the standardized Levins index was equal to 0.59, which indicates a diet not specialized in this area of the animal. The absence of large animals in the diet of pumas, which are commonly found, suggesting low habitat quality, probably caused by the strong human pressure, due to the exploitation of the area or even hunting

No Brasil, a onça-parda, Puma concolor (Linnaeus, 1771) está presente em todos os biomas. A capacidade da onça-parda em se adequar a diferentes tipos de habitats tem levado a espécie cada vez mais a utilizar áreas antropizadas em busca de alimento e abrigo, principalmente áreas de reflorestamento com espécies exóticas como pinheiro e eucalipto. As principais ameaças encontradas pelos felinos são a fragmentação e modificação do hábitat, principalmente nos biomas Mata Atlântica e Cerrado, e a caça indiscriminada. A dieta de uma espécie é um dos aspectos mais básicos de sua ecologia, mas permeia quase todos os parâmetros ecológicos, como o sistema social, espacial e padrões de atividade, por isso pode ser considerada essencial para a compreensão de sua ecologia, bem como pode auxiliar em planos de manejo e conservação de áreas e espécies. O objetivo do presente trabalho é o de caracterizar a dieta da onça-parda em uma unidade de manejo florestal que está situada em uma área de contato entre Cerrado e Mata Atlântica, através de material escatológico. As amostras foram coletadas de abril a setembro nos anos de 2007 e 2008, em uma unidade de manejo florestal no município do Borebi-SP, totalizando 10 amostas. Após a analise do material obtivemos 16 ocorrências de 8 itens alimentares sendo que a maior porcentagem de ocorrência foi de mamíferos (62,5%), principalmente Dasypus novemcinctus (Linnaeus, 1758), considerada como o principal item alimentar segundo a frequência de ocorrência das presas e porcentagem de biomassa consumida, o índice padronizado de Levins foi igual a 0,59, o que aponta uma dieta não especializada do animal nessa área. A ausência de animais de grande porte na dieta da onça-parda, que são comumente encontrados, sugere baixa qualidade do habitat, provavelmente causada pela forte pressão humana, devido à exploração da área ou até mesmo à caça
Keywords: Animais - Alimentos; Puma; Ecologia animal; Habitos alimentares; Animal ecology